Effectiveness of the organization and its role in achieving the requirements of Strategic success: A survey study of the opinions of a sample of workers at the Asia Telecom Company in Baghdad (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The research aims present to highlight the importance of creating construction Organizational appropriate to achieve strategic success and reduce many of the negative effects experienced by organizations has been developing his questionnaire especially so was distributed to a sample of workers in the Asia-cellular as sample included (60) responsive 0 and can embody intellectual dilemma following questions (What are the dimensions of the organizational infrastructure, and what are the justifications for carrying out the reform and development cleared the organizational structure to make it more flexible) to contribute to the achievement of the strategic requirements for success of the organization surveyed. Find recommended a number of conclusions and recommendations